2019
DOI: 10.1029/2019jd030566
|View full text |Cite
|
Sign up to set email alerts
|

Release of Perfluoroalkyl Substances From Melting Glacier of the Tibetan Plateau: Insights Into the Impact of Global Warming on the Cycling of Emerging Pollutants

Abstract: The Tibetan Plateau (TP) has encountered rapid warming, with more than 50% of lakes expanding and 80% of glaciers retreating. Melting glaciers are known as a secondary source of pollutants, but the dynamics and release features of water‐soluble emerging chemicals have not been studied in the TP. Glacial ice and snow, meltwater runoff, rain, and lake water were collected in Nam Co basin, in the central TP. The total concentrations of perfluoroalkyl acids (PFAAs) were 1,413 pg/L for glacial ice, followed by 1,27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…Snow deposition is limited to cold regions and/or cold periods of time, while rain precipitation occurs widely for different seasons and across climatic regions. Furthermore, there are observations that concentrations in rivers increase after strong rain events. ,,, Such large concentrations would be driven by the amplification of POPs by rain and the focusing of water in rivers from the watershed. Future work should be focused on studying the role of wet deposition on the cycle and occurrence of organic pollutants, especially in terms of its spatial and temporal dynamics, and extending this assessment to chemicals of emerging concern.…”
Section: Resultsmentioning
confidence: 99%
“…Snow deposition is limited to cold regions and/or cold periods of time, while rain precipitation occurs widely for different seasons and across climatic regions. Furthermore, there are observations that concentrations in rivers increase after strong rain events. ,,, Such large concentrations would be driven by the amplification of POPs by rain and the focusing of water in rivers from the watershed. Future work should be focused on studying the role of wet deposition on the cycle and occurrence of organic pollutants, especially in terms of its spatial and temporal dynamics, and extending this assessment to chemicals of emerging concern.…”
Section: Resultsmentioning
confidence: 99%
“…The Tibetan Plateau (TP) contains the largest volume of glaciers outside the polar regions and has underwent rapid warming during the past 2 decades . Previously, studies have presented evidence that Tibetan glaciers continuously release trace toxicants and hydrophilic contaminants such as mercury and perfluoroalkyl substances into lakes. , On the other hand, microplastics had been found in the Tibetan glacier, lakes, , and a few rivers . However, these studies mainly reported the concentrations and compositions of microplastics in either glacier ice or lake/river waters, without consideration of the atmospheric fallout and glacier runoff.…”
Section: Introductionmentioning
confidence: 99%
“…The global signature of chemical pollution emergent from the cryosphere is increasing as melt progresses [ 35 ]. High alpine and Polar environments see the most disproportionate warming [ 37 , 38 ], but are also the most critical global water towers, distributing water to millions of people [ 39 ].…”
Section: Chemical Risksmentioning
confidence: 99%